A bedside test for methaemoglobinemia improved antidote use in propanil poisoning. (8th August 2016) - Shihana, Fathima; Dawson, Andrew H.; Dobbins, Timothy; Dissanayake, Dhammika; Buckley, Nicholas A.
Abstract: Background: In 2008, self-poisoning with the herbicide propanil had a case-fatality of around 11% in Sri Lanka. A simple quantitative methaemoglobinemia bedside test was developed so that treatment could be titrated according to the methaemoglobin level. Objective : To determine whether the new method influenced patient management and changed the case fatality of propanil self-poisoning. Method: The bedside test (using an inexpensive validated colour chart) was introduced in three hospitals (Anuradhapura, Polonnaruwa and Galle) in Sri Lanka from 2008. Junior ward staff were given a brief training on how to use the chart for quantitative estimation of methaemoglobin in patients with propanil poisoning and utilize the results in the context of the national treatment guidelines for propanil poisoning. It was taught that the bedside test should be done repeatedly from admission until it showed consistently low values of methaemoglobin. Treatment with the antidote methylene blue was suggested for patients whose methaemoglobin was greater than 20%. Limited clinical data on poisoning have been prospectively collected from these hospitals from 2003. The case-fatality and management before and after the change were compared with data up to December 2014. Results: The case-fatality decreased from (38/401) 9.5% to (8/262) 3.1% [difference: −6.4%, 95% CI: −10 to −3]. Methylene blue use increased from under 10% of patients before to 55% of patients after the intervention. More patients received repeat doses and infusions, and few received ascorbic acid and exchange transfusion. Conclusion: The simple bedside test for methaemoglobinemia was readily adopted into routine practice and led to large changes in management. A substantial reduction in mortality from propanil poisoning occurred after this intervention.